Pengendali Robot dengan Mikrokontroler Arduino Berbasis Smartphone Android - Bambang Setyo Panulisan; Rizki Fajar Akmal; Wiwien Suzanti; Yolla Sukma Handayani; Asep Rahmatullah; Hamdan Hamdan; Wizuna Aji Sea Santosa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The rapid development of technology has given rise to automatic robots controlled by wireless technology. Many electronic devices are used as automatic controllers. This robot, produced in the electronics field, has had a rapid impact in the industrial sector. In this research, Arduino Uno is used as a microcontroller to control robots with Android smartphones. Control is carried out using a Bluetooth connection. The use of Android smartphones makes it easier for the general public if the results of this research are applied because many people have Android smartphones. Apart from being easy to use, this robot can also help human work. The pattern used for smartphone communication with Bluetooth hardware. The smartphone sends data via Bluetooth, then the HC-05 Bluetooth receives the data forwarded to the Arduino Uno microcontroller, then the microcontroller processes it to give moving commands to each servo motor. The application used to control the robot is NodeMCU_Car. This application is implanted into an Android smartphone so that robot movement commands can be carried out via the smartphone with this application. Robot movement commands are carried out manually by the operator. The robot can move to open or close its arms. Tests were carried out on the power supply circuit, Bluetooth, power supply, and the entire robot circuit. This research shows that the robot's electronic circuit is functioning well, such as the Bluetooth component circuit, power supply and controller circuit. The maximum distance that a Bluetooth device can receive smartphone data without obstacles is 9 meters, whereas if there are obstacles the distance is 5 meters.Keywords: Arduino, Bluetooth, Electronics, Microcontroller, Smartphone